Analysis of the global economic crisis using the cox proportional hazards model - Wachirawit Puttachai (2019)
© Springer Nature Switzerland AG 2019. This paper uses the Cox proportional hazards model to examine which of the structural characteristics could resist the US financial crisis survival countries. The dependent variable in this model is generated from GDP, and the Markov Switching Autoregressive (MS-AR) technique is used to detect the survival period as well as the crisis occurrence in each country. The survival of a country is found to be influenced by continents (Asia, Australia and Africa) and the higher development level. However, being the member of economic communities, APEC and WTO, increase the chance of the crisis occurrence.